2014
DOI: 10.1089/biores.2014.0050
|View full text |Cite
|
Sign up to set email alerts
|

In VivoEctopic Bone Formation by Devitalized Mineralized Stem Cell Carriers Produced Under Mineralizing Culture Condition

Abstract: Functionalization of tissue engineering scaffolds with in vitro–generated bone-like extracellular matrix (ECM) represents an effective biomimetic approach to promote osteogenic differentiation of stem cells in vitro. However, the bone-forming capacity of these constructs (seeded with or without cells) is so far not apparent. In this study, we aimed at developing a mineralizing culture condition to biofunctionalize three-dimensional (3D) porous scaffolds with highly mineralized ECM in order to produce devitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…Higher expression of BMP‐2 was detected in the MECS group compared with the CS group, and osteogenic induction significantly increased BMP‐2 expression levels in both groups. These findings indicate that mineralized ECM could provide a cell‐instructive structural framework that induces stem cell osteogenic differentiation …”
Section: Resultsmentioning
confidence: 80%
“…Higher expression of BMP‐2 was detected in the MECS group compared with the CS group, and osteogenic induction significantly increased BMP‐2 expression levels in both groups. These findings indicate that mineralized ECM could provide a cell‐instructive structural framework that induces stem cell osteogenic differentiation …”
Section: Resultsmentioning
confidence: 80%
“…33,34 In fact, our previous study has provided a ''proof-of-principle'' that 3D porous scaffolds bearing cellsecreted mineralized ECM were readily recognized by the host environment as an ''osteogenic biotemplate'' and triggered bone formation. 21 The limited bone formation on the carriers (<1% per total scaffold void volume of 64.8 mm 3 ) served as our motivation to further optimize the mineralizing culture condition in this study. As a result, we showed that the current modified culture protocol (i.e., combining the priming followed by a direct mineralization phase) augmented nearly five-fold ectopic bone formation on the carriers as compared with the previously reported direct culture mineralization method.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we assessed the ectopic bone induction and critical-sized calvarial defect bridging capacities of the produced devitalized mineralized carriers by using an immunocompromised large rodent model, that is, athymic nude rats (as compared with only ectopic implantation in nude mice in our previous study 21 ). This model was beneficial to avoid immunorejection of the hPDC-seeded carriers due to untoward immune responses on the transplanted human cells.…”
Section: Assessment Of Ectopic Bone Induction and Critical-sized Calvmentioning
confidence: 99%
See 2 more Smart Citations